Gas-dynamic roof fall during the potash deposits development - Alexander A. Baryakh; Sergei S. Andreiko; Anton K. Fedoseev (Записки Горного института, 2020)
In the development of practically all potash salt deposits, the study of gas-dynamic phenomena (GDP) is one of the most difficult tasks to ensure mining safety. Sudden salt and gas outbursts, dynamic breakdown, which are accompanied by intense gas release and possible broken rock carry-over into the mine workings, are associated with GDP. Geological preconditions for the GDP development are often the layered structure of the salt rock mass, the presence of interlayers and layers of salt clays.